Jesus and his promised Second Coming Jewish eschatology and Christian origins - Ferda, Tucker S.; Allison, Dale C. (Chicago William B. Eerdmans Publishing Company, 2024)
"An examination and rebuttal of the critical consensus that Jesus of Nazareth did not predict or anticipate his post-death return"--
"In this pioneering study of Scripture and reception history, Tucker S. Ferda shows that the hope for Jesus's second coming originated in his own message about the coming of the kingdom after a time of distress. Most historical Jesus scholars take for granted that Jesus's second coming was invented by his zealous early followers. In Jesus and His Promised Second Coming, Tucker S. Ferda challenges this critical consensus. Using innovative methodology, Ferda works backward through reception history to Paul and the Gospels to argue that the hope for the second coming originated in Jesus's own grappling with the prospect of death and his conviction that the kingdom was near; he expected a return that would coincide with the final judgment and the end of the age within the space of a generation. Ferda also makes a major contribution to the reception history of the Bible, shedding light on how Christians distinguished themselves from Judaism by deriding "Jewish messianism" as earthly minded and militaristic. In the early modern period, critics found an expedient way to distance Jesus from this caricature of "Jewish messianism": they pinned the expectation for the second coming on Jesus's early followers. A new appreciation for the diversity of Judaism and messianism in the Second Temple period makes possible a fresh reconstruction of Jesus. Bold and historically astute, Jesus and His Promised Second Coming breathes new life into a long-stagnant conversation. It also offers readers fresh insight into the history of Jewish-Christian relations. Students and scholars of the New Testament will need to read and engage with Ferda's provocative argument"--
Description based on publisher supplied metadata and other sources
Keywords: Bible -- Criticism, interpretation, etc; Eschatology; Eschatology, Jewish; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; RELIGION / Biblical Studies / New Testament / Jesus, the Gospels & Acts; RELIGION / Christian Theology / History